Old Yeller - Gipson, Fred, 1908-1973. (New York HarperCollins, 2004)
The story of a boy and his dog in the Texas hill country of the 1860s.
Q
b
b
Keywords: Human-animal relationships -- Fiction; Boys -- Fiction; Dogs -- Fiction; Western stories; Bildungsromans